53‐4: Image Saliency Detection based Depth Adjustment for Stereoscopic Image. Issue 1 (May 2016) - Xia, Zhenping; Cheng, Cheng; Hu, Fuyuan; Zhang, Zhancheng
Abstract : Considering the improper depth distribution caused eye fatigue, we proposed a novel stereoscopic depth adjustment method to improve the visual comfort and enhance viewing experience. The proposed method combined the image saliency and specific viewing condition to establish a novel model for computing the optimum zero‐disparity plane of stereoscopic image.